Simbol dalam Tenun Ikat: Perspektif Interaksionisme Simbolik terhadap Desain Tenun Ikat pada Undangan Karya Siswa SMKN 4 Kupang - Herman Menno; Aloysius Liliweri; Syarifudin Drajad (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Tenun Ikat is not just a fabric, but a reflection of the identity, beliefs, and noble values of the local community. Each motif, color, and pattern woven into the ikat has a strong symbolic meaning, telling the stories of ancestors, customary rituals, and the worldview of the community. This research aims to identify the symbolic meanings of ikat weaving used in the invitation designs created by students of SMKN 4 Kupang. It analyzes the role of social interaction in shaping the meaning of ikat symbols. in the design of invitations and examining the implications of using ikat weaving symbols for the preservation of local culture in Kupang. This research employs a qualitative approach of Symbolic Interactionism. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation involving students, teachers, local weavers, and local designers. The results of this research indicate that the utilization of traditional ikat weaving motifs in the digital wedding invitation design by students of SMKN 4 Kupang is not merely an aesthetic trend, but rather a profound cultural process. Through Roland Barthes' semiotic approach, it is revealed that the weaving motifs (Katak Ayotupas, Belis Danu, and Mamuli) possess layers of rich symbolic meaning, from literal denotation to cultural myths that are deeply rooted in local identity and spirituality. The symbolic meaning of the motifs is not created individually. Instead, this meaning is negotiated and enriched through collective dialogue. This interaction transforms the historical and emotional context that transforms motifs into a living heritage. The implications of preserving local culture, through the use of ikat weaving in modern media such as digital invitations, serve as an indirect educational tool for the community, reinforcing the cultural identity of the couple and strengthening cultural ties that may begin to fade. Thus, this research concludes that the design of digital invitations can be an effective medium to bridge tradition and modernity, ensuring that cultural heritage remains relevant, authentic, and continues to thrive in the digital era.